Scope of the Use of Research Methods in the Process of Developing Innovation Products and the Possibilities of Using it in Researching Social Media - Słupińska (Peszko), Kamila; Szwajlik , Anna (Studia Oeconomica Posnaniensia, 2017)
The purpose of the article is to look at the process of developing innovation products by the qualitative research methods used. The authors in the article present the results of research conducted by innovative companies on the research methods used in the process of the development of innovation and the degree of involvement of users in the creation of goods or services to study the correct direction of development. In addition, the research presents opinions on the use of social media channels in the research process and developing innovation products. The final conclusions are the opinions of the authors on the possibilities of improving the process of developing innovation products by using selected research methods in conjunction with social media as a communication channel.